Jawabanmu

2014-09-13T20:27:06+07:00
 p =  \sqrt{1- \frac{1}{x} \sqrt{1- \frac{1}{x} \sqrt{1- \frac{1}{x} \sqrt{1- \frac{1}{x} }  }  }  -\\  \\ \\   p^{2} =  {1- \frac{1}{x} \sqrt{1- \frac{1}{x} \sqrt{1- \frac{1}{x} \sqrt{1- \frac{1}{x} }  }   }  \\  \\  p^{2}=1  -  \frac{1}{ \sqrt{3} }  . p =  \frac{( \sqrt{3} -p) }{ \sqrt{3}}  \\  \\ =

 p^{2}  \sqrt{3} = ( \sqrt{3} -p \\  \\ p²√3 +p -√3=0.....

dngan rumus abc p1= (-1+ √(1 - 4√3 .(-√3))/(2√3)

p1= (-1 + √13)/(2√3) = 1/6(-√3 +√39)=1/6(√39-√3)

p2 =(-1 - √13)/(2√3) = 1/6(-√3 -√39) ... tak mungkin hasil negatif

1 5 1